THE POTENTIAL ECONOMIC ANALYSIS OF SOLAR HOME SYSTEM WITH SWITCHING METHOD ON HOUSEHOLD ELECTRICITY SCALE - Kurnia Paranita Kartika; Riska Dhenabayu (JURNAL MANAJEMEN DAN BISNIS, 2020)
This study aims to design a Solar Home System with an Arduino-based Smart Switching system so that the use of electrical energy generated by solar panels can be adjusted without adding power from other electricity sources, such as PLN. Calculation of Leveled Cost of Energy (LCOE) is used as the basis for the switching process that will be carried out to regulate the use of household appliances that are routinely used, regulate electricity consumption automatically, minimize usage, and calculate the effectiveness of electric power usage. The way SHS works is to collect electrical energy from sunlight, then convert DC voltage to AC so that it can be used to run household electronic equipment. To accommodate the adequacy of electrical power, an automatic adjustment is made for household appliances that are routinely used, namely house lights, which includes setting the lights on and off and the number of lights that can be activated. The advantage of this research is that the SHS system is integrated with the automatic setting of the lights installed in the house so that the number of lights on will adjust the availability of electrical energy in the battery. In addition, with the LCOE method, the level of usage can be calculated so that users can save electricity. From the results of usage testing, it is found that the application of this switching technology provides benefits for users because it is no longer dependent on PLN supply. From an economic point of view, based on the calculation of Leveled Cost of Energy (LCOE), there is a kWh value savings of Rp. 77, - for each kWh price or about 4.53% compared to purchasing electricity with prepaid mode.